Mobile Cloud Computing Reliability Enhancement: A Study Of Existing Techniques Including Shadow Cores - Kaur, Ramanpreet; Kaur, Kiranbir (International Journal of Computer Sciences and Engineering, 2025)
As the interest for mobile cloud computing keeps on expanding, cloud specialist organizations confront the overwhelming test to meet the arranged SLA agreements, as far as dependability and convenient .execution, while accomplishing cost and energy efficiency. This paper proposes Shadow Replication, a novel fault-tolerance mechanism for Mobile cloud computing, which flawlessly address fault at scale, while limiting energy utilization and lessening its effect on cost. Energy conservation is achieved by creating dynamic cores rather than static cores. Cores are created by the application of cloudlets. In other words proportionate cores are created. Core failure metrics are considered to be memory capacity, energy and power consumption. In case any of the parameter exceeded threshold value, core is supposed to be faulted and progress is maintained within shadow which is maintained 1 per host. Progress of deteriorated Core is shifted to next core within other VM. In case all the core within VM deteriorated, VM migration is performed. Comparative study of techniques used to establish reliability within MCC is presented for future enhancements in terms of latency, downtime and migration time.